Desain Pembelajaran Penjumlahan dan Pengurangan Bilangan Menggunakan Konteks Bangka Belitung untuk Mendukung KBKM Siswa - Rajab Vebrian; Yudi Yunika Putra (Jurnal Pendidikan Matematika:Judika Education, 2019)
This study aims to produce learning trajectories of addition and subtraction of material numbers using the context of Bangka Belitung, also to find out whether the use of these learning designs can support students' Critical Thinking Abilities (KBKM). The research method, this research is a validation study design research type involving 6 students in the pilot experiment stage, and 25 students in the teaching experiment stage. The alleged learning trajectory was developed from a series of learning activities using the context of the Pacific Islands, such as sahang / pepper seeds as a model in learning the addition and subtraction of numbers. The results showed the use of trajectories in the context of Bangka Belitung provided different assessment results between the students' pretest and posttest scores. Most students have been able to solve the problem of addition and subtraction and provide arguments in answering the problems encountered. In conclusion, the use of instructional design using the context of Bangka Belitung in the learning of addition and subtraction of numbers can support student CBCS. Keywords: Numbers, Design, Learning Context